2020
DOI: 10.1155/2020/5651737
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of Nuts at Midlife and Healthy Aging in Women

Abstract: Background. Nut consumption may reduce age-related diseases and lead to better health and well-being in aging. Many conditions of aging develop over decades, and thus earlier lifestyle factors may particularly influence later health. Methods. In 1998 and 2002, we administered food frequency questionnaires to assess nut consumption (peanuts, walnuts, and other nuts and peanut butter) in women in the Nurses’ Health Study in their 50 s/early 60 s. In 2012, those who survived beyond 65 years with no chronic diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Freitas-Simoes and colleagues reported a significant positive association between walnut consumption and odds of healthy aging (defined as surviving beyond 65 years of age with no history of 11 chronic diseases, no self-reported memory impairment, no physical disabilities, and intact mental health) among participants of the NHS (odds ratio [OR] = 1.20, 95% CI 1.00–1.44, comparing ≥2 servings/week vs no walnut consumption, P for trend = 0.0001, fully adjusted model). 104 Higher consumption of walnuts was significantly associated with lower odds of physical function impairment (measured using the physical function domain of the SF-36 questionnaire, which assesses physical limitations in performing daily activities) among participants of the HPFS (OR = 0.80, 95% CI 0.68–0.94, comparing ≥2 servings/week vs never or <1 serving/month, P for trend = 0.01, fully adjusted model). 99 Finally, secondary analysis of the Health and Retirement Study and Health Care and Nutrition Study reported an association between walnut consumption and cognitive function.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations
“…Freitas-Simoes and colleagues reported a significant positive association between walnut consumption and odds of healthy aging (defined as surviving beyond 65 years of age with no history of 11 chronic diseases, no self-reported memory impairment, no physical disabilities, and intact mental health) among participants of the NHS (odds ratio [OR] = 1.20, 95% CI 1.00–1.44, comparing ≥2 servings/week vs no walnut consumption, P for trend = 0.0001, fully adjusted model). 104 Higher consumption of walnuts was significantly associated with lower odds of physical function impairment (measured using the physical function domain of the SF-36 questionnaire, which assesses physical limitations in performing daily activities) among participants of the HPFS (OR = 0.80, 95% CI 0.68–0.94, comparing ≥2 servings/week vs never or <1 serving/month, P for trend = 0.01, fully adjusted model). 99 Finally, secondary analysis of the Health and Retirement Study and Health Care and Nutrition Study reported an association between walnut consumption and cognitive function.…”
Section: Resultsmentioning
confidence: 94%
“…The characteristics of the cohort studies can be seen in Table S15 in the Supporting Information online. Cohort studies were conducted in the United States (Nurses’ Health Study [NHS], Nurses’ Health Study II [NHS II], Health Professionals’ Follow-up study [HPFS], 33 , 66 , 99 , 103 , 104 Coronary Artery Risk Development in Young Adults [CARDIA] study, 102 Health and Retirement and Health Care Nutrition studies 101 ) Iran (Golestan Cohort Study, Tehran Lipid and Glucose Study 100 , 105 ), and 1 measured walnut consumption in Argentina, Bangladesh, Brazil, China, Iran, Poland, Saudi Arabia, Turkey, and the United Arab Emirates (the Prospective Urban and Rural Epidemiology [PURE] study 98 ) All assessed walnut intake using food frequency questionnaires, which were self-administered in 6 cohorts, and interviewer-administered in 2 cohorts (CARDIA study 102 and Tehran Lipid and Glucose Study 105 ). One cohort study exclusively enrolled older adults.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is evidence from a single prospective study conducted in Spain, where nut consumption is rather high, that it may lower the risk of impaired agility/mobility and increase overall physical function in older individuals [ 102 ], while another report from the NHS cohort suggests that consumption of total nuts and, particularly, walnuts is associated with healthy aging, i.e., survival beyond 65 years with no chronic diseases, no memory impairment, no physical disabilities, and intact mental health [ 103 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%
“…Finally, we asked whether personal NR can be an indicator of healthy aging ---an overall indicator we developed by combining measures of physical function, cognitive function, mental health, and chronic diseases [51][52][53] . To address this question, we focused on a subset of NHS participants (n=21,299) for whom we had all of these four healthy aging components: healthy agers (n=3,491) and usual agers (n=17,808) through a previous study 54 . The healthy agers are defined as those participants who survived beyond 65 years of age, with no history of chronic diseases, no reported memory impairment, no physical disabilities, and intact mental health.…”
Section: Impact Of Food Composition On Personal Nrmentioning
confidence: 99%